Strengthening the Relationship with Parents; School Creativity to Overcome School’s Infrastructure Problems - Sri Widayati; Suryanti Suryanti; Wiryanto Wiryanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to describe the creativity of an elementary school institution in establishing relationships with parents in overcoming the problems of facilities and infrastructure before and during the COVID-19 pandemic and post-pandemic. Completeness of facilities and infrastructure will support the achievement of learning objectives. This research is descriptive and qualitative with the subject of this research being SDN Kota Baru IX, Bekasi City. Data collection techniques use interviews, observation, and documentation with data analysis using triangulation. The results of this study reveal that online learning at SDN Kota Baru IX, Bekasi City does not experience difficulties, this is supported by the various creative ideas of teachers under the auspices of the PMPS (School Education Quality Assurance) team which is well coordinated with parents. Parents fully support online learning by providing various facilities such as wifi, android/ios-based cellphones, and laptops. Parenting education is the key to bridging communication with parents. This research implies that schools that have good cooperation with parents will have an impact on the success of school programs in dealing with various situations.